Providing microfinance and social space to empower adolescent girls: An evaluation of BRAC’s ELA centres - Shahnaz, Rizwana; Karim, Raihana (BRAC Research and Evaluation Division, 2022)
Lately there has been a surge in the variety of approaches to assist the adolescents, specially the girls, in building up their lives and livelihoods. With financial assistance from Nike Foundation, BRAC started combining financial and social interventions in 2005 by setting up ELA (Employment and Livelihood for Adolescents) Centres for the ELA microfinance group members. This study is intended to assess the usefulness of this combined approach. It is based on a panel dataset of ELA Centre participants and non-participants, which tried to capture changes using qualitative tools. Despite a number of methodological drawbacks, we found indication of the programme being useful in reducing the chances of early marriage, engaging the participants in economic activities, increasing their mobility and involvement in extracurricular reading. Qualitative exploration indicated much stronger effects than our survey estimates, which may have happened because of the participants’ over-attribution of their status on their participation, which is biased by self-selection. On the other hand, there are some indications that the surveys failed to capture some changes due to methodological limitations. Nonetheless, it appears that girls at disadvantaged position in terms of education and parents’ openness to girl’s empowerment are less likely to participate in the programme. It points the need for targeting such girls. Moreover, the skill development training should include a generic module on financial literacy focusing on budgeting, financial management, insurance schemes etc. There is still scope of improvement in general awareness on health issues. The materials that are provided to the centre should include more health specific knowledge based issues.